Airline Fleet Assignment and Schedule Planning - majid, suharto abdul; Nugroho, Aditya (STMT Trisakti, 2014)
Airline fleet assignment plays important role for efficient operation of airlines. In order tosave costs from the procurement and maintenance of extra aircrafts, the airline operatorswould always seek to minimise the fleet size, while at the same time being able to operateall the flights without shortage of aircraft. Therefore, the daily flight schedule of the airlinemust be prepared in such a way that the destinations can be served with minimum numberof aircrafts. Considering this, there is huge prospect of using optimisation techniques toselect the optimum mix of various types of aircrafts in the airline fleet and thereby toproduce an optimum flight schedule.Keywords: Integer Linear Programming, Fleet Assignment Model (FAM) algorithms.Integrated Schedules Design (ISD), Extended Schedules Design (ESD) algorithms.